The effect of terminal impedance on aortic morphology and hemodynamics: an in vitro phantom study using flow field visualization - Chen, Huimin; Wang, Wenjun; Liu, Dengji; Cao, Zhen; Yang, Yi; He, Ying; Chi, Qingzhuo (Frontiers in Bioengineering and Biotechnology, 2023)
To investigate the risk factors of the tearing of aortic dissection, we fabricate a simplified patient-specific aortic silicone phantom by the Brush-Spin-Coating method. The aortic phantom only contains the aorta from ascending aorta to descending aorta without other branches. We design two experiment systems to access the alteration of aortic morphology and the intravascular hemodynamics by particle image velocimetry (PIV). The experiment results show the dilation and elongation of the aortic phantom after increasing the terminal resistance, especially the inner side of the aortic arch. PIV results also show the increase of the vortex region, resulting in the inner side of the aortic wall being scoured by the blood. The work suggests that the deformation of the inner side aortic wall and the hemodynamics change by the terminal increase may be the risk factor of tearing and should be noticed.